The cosmic script : sacred geometry and the science of Arabic penmanship - Moustafa, Ahmed, 1943- (Inner Traditions, 2014)
"A fully illustrated, landmark study of Islamic calligraphy traced back to its deepest historical and cultural roots Explores the sacred geometry of each letter form of the Arabic alphabet as attributed to renowned 10th-century scribe Ibn Muqla Traces Ibn Muqla's system to the cross-cultural encounter between Greek learning and the scientific, artistic, and philosophical pursuits of classical Islam A richly illustrated, two-volume presentation of decades of research with more than 430 full-color illustrations Calligraphy is the central visual art of Islam. At its core resides a perennial challenge: What letter shapes traced by human hands are rightful bearers of the divine message? The answer lies in the "Proportioned Script" of Ibn Muqla, renowned scribe, man of letters, and minister under the great Abbasid Caliphate in 10th-century Baghdad. Emphasizing harmony and geometry, Ibn Muqla's system has governed the practice of Arabic scribal art up to the present day. In this two-volume, richly illustrated study, Ahmed Moustafa and Stefan Sperl analyze each letter form of Ibn Muqla's perfected penmanship and share their decades of research on Islamic letter shapes, revealing the history, linguistics, philosophy, theology, and sacred geometry that underlie this spiritual art form. In volume one the authors reveal the trilogy of prophecy, penmanship, and geometry at the foundation of Ibn Muqla's Proportioned Script. Providing a fully illustrated analysis of Islamic calligraphy's geometrical principles as transmitted in surviving writings and key manuscript sources, they examine the geometric grid of square, circle, and hexagon that informs the pen strokes of each letter shape and explore how the golden ratio appears within the matrix of the grid. They examine the development of Ibn Muqla's system in the context of the sciences, arts, and penmanship of 10th-century Baghdad and trace its origins to the cross-cultural encounter between Greek learning and the scientific, artistic, and philosophical pursuits of classical Islam. In volume two the authors analyze the calligraphic forms of each letter of the Arabic alphabet. They decode the sacred geometry of each form as it appears within the geometric grid, providing letter samples from ancient sources. Unearthing the theoretical and scientific foundations of Arabic calligraphy, this landmark study examines the aesthetic implications of Ibn Muqla's theory for the visual, verbal, and aural arts of Islam as well as the Islamic mystical tradition"--